2004
DOI: 10.1575/1912/2065
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of scalar transfer coefficients in fog during the Coupled Boundary Layers and Air Sea Transfer Experiment : a case study

Abstract: The uncertainty in the determination of the momentum and scalar fluxes remains one of the main obstacles to accurate numerical forecasts in low to moderate wind conditions. For example, latent heat fluxes computed from data using direct covariance and bulk aerodynamic methods show that there is good agreement in unstable conditions when the latent heat flux values are generally positive. However, the agreement is relatively poor in stable conditions, particularly when the moisture flux is directed downward. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The ABL over the CBLAST region was typically stable during the first half of the summer resulting from the combination of advection and a slowly warming coastal ocean (Crofoot 2004). This is a common occurrence along the East Coast during the late spring and early summer.…”
mentioning
confidence: 99%
“…The ABL over the CBLAST region was typically stable during the first half of the summer resulting from the combination of advection and a slowly warming coastal ocean (Crofoot 2004). This is a common occurrence along the East Coast during the late spring and early summer.…”
mentioning
confidence: 99%
“…Under weak stable conditions, moisture flux was mostly negative and varied proportionally with sensible heat flux (linear correlation R 2 = 0.68). The observed downward fluxes corresponded to air flows from warmer towards cooler waters upwind the south measuring site and it should be mentioned that downward latent heat fluxes with values one order of magnitude greater have been observed to respond to sea fog events (Crofoot 2004). It is also worth to mention that similar studies of turbulent measurements of moisture under relevant conditions are not often found in the international literature.…”
Section: Surface Heat and Moisture Fluxesmentioning
confidence: 70%
“…measurement mast unstable conditions are often present due to cold air advecting above the much warmer ocean, this is consistent with other locations in the North-Sea (Patton et al, 2015;Barthelmie, 1999). However, for the ASIT measurement mast stable conditions do occur often in late spring to early summer when the ocean is slowly warming by warm ocean water flowing over the colder ocean, typically identified with cool summer weather and fog (Edson et al, 2007;Crofoot, 2004). The integrated stability function can be calculated by Eq.…”
mentioning
confidence: 99%